Tax Avoidance: Is There a Difference Between Indonesia, Thailand, and Philippines? - Cahyani, Ardhia Pramesti Regita; Faisol, Moh. (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Purpose: This study aims to analyze a comparative comparison of tax avoidance practices in manufacturing companies in Developing Countries in the Asian Region, especially in Indonesia, Thailand, and the Philippines during the covid-19 pandemic (2020-2022 period). Method: This study uses a quantitative approach by analyzing the comparison of tax avoidance in Indonesia, Thailand, and the Philippines using the Independent Sample t Test. The measurement of tax avoidance uses CETR. Results: The results of the study found that there was a significant difference in the level of tax avoidance between manufacturing companies in Indonesia and Thailand, manufacturing companies in Indonesia and the Philippines, but there was no difference in tax avoidance between manufacturing companies in Thailand and the Philippines. Implications: As a reference for the Directorate General of Taxes and investors related to the motives for tax avoidance carried out by manufacturing companies in three countries during the covid-19 pandemic. Novelty: This study uses financial data of manufacturing companies during the covid-19 pandemic in three Developing Countries in Asia.